Early and long-term outcomes of conventional and valve-sparing aortic root replacement. Issue 23 (17th May 2022) - Jahangiri, Marjan; Mani, Krishna; Acharya, Metesh; Bilkhu, Rajdeep; Quinton, Paul; Schroeder, Frank; Morgan, Robert; Edsell, Mark
Abstract : Objective: To determine the early and long-term outcomes of conventional aortic root (ARR) and valve-sparing root replacement (VSRR) using a standard perioperative and operative approach. Methods: We present prospectively collected data of 609 consecutive patients undergoing elective and urgent aortic root surgery (470 ARR, 139 VSRR) between 2006 and 2020. Primary outcomes were operative mortality and incidence of postoperative complications. Secondary outcomes were long-term survival and requirement for reintervention. Median follow-up was 7.6 years (range 0.5–14.5). Results: 189 patients (31%) had bicuspid aortic valves and 17 (6.9%) underwent redo procedures. Median cross-clamp time was 88 (range 54–208) min with cardiopulmonary bypass of 108 (range 75–296) min. In-hospital mortality was 10 (1.6%), with transient ischaemic attacks/strokes occurring in 1.1%. In-hospital mortality for VSRR was 0.7%. 12 patients (2.0%) required a resternotomy for bleeding and 14 (2.3%) received haemofiltration. Intensive care unit and hospital stay were 1.7 and 7.0 days, respectively. During follow-up, redo surgery for native aortic valve replacement was required in 1.4% of the VSRR group. Overall survival was 95.1% at 3 years, 93.1% at 5 years, 91.2% at 7 years and 88.6% at 10 years. Conclusions: ARR and VSRR can be performed with low mortality and morbidity as well as a low rate of reintervention during the period of long-term follow-up, if performed by an experienced team with a consistent perioperative approach. This series provides contemporary evidence to balance the risks of aortic aneurysms and their rupture at diameters of <5.5 cm against the risks and benefits of surgery.